Peningkatan Sikap Terkait Kebersihan Gigi Melalui Media Edukasi Whosit Game di SDN Kertajaya IV - Hayatunnufus; Sendia Martina, Yulyana; Laily, Rohisotul; Septiarini, Dwi (Jurusan Keperawatan Gigi Poltekkes Kemenkes Makassar, 2025)
The prevalence of dental caries in Indonesia, especially among 10-14 year olds, is 37.2%. Health promotion is an effort to ensure that the community has the willingness and ability to maintain and improve their own health. One of the health promotion strategies is health education. The purpose of this study was to examine the effectiveness of the Whosit Game educational media in improving students' attitudes towards dental and oral health. This study was an analytical study with a pre-experimental design. The research subjects involved 45 fourth-grade students at SDN Kertajaya IV Surabaya with a paired T-test. The results showed a significant increase in students' attitudes before and after being given whosit game education with a p-value of 0.000. It can be concluded that providing education using whosit game media is effective in improving students' attitudes towards dental and oral hygiene. Keywords : Whosit game; Attitude; Dental and Oral Hygiene; Students